A PARP inhibitors in the treatment of breast cancer - A Review of literature - Niewiadomska, Jagoda; Bondos, Borys; Stępień, Aleksandra; Paluch, Alicja; Skrzypek, Jakub; Niekra, Aleksandra; Fussek, Łukasz; Kochan, Robert; Wieczorek, Ewelina; Lee, Kacper (Journal of Education, Health and Sport, 2024)
Introduction Breast cancer is the most common malignancy in women in developed countries. It also occurs in men. The primary therapy for these cancers is surgery; chemotherapy, radiation therapy, hormone therapy, or immunotherapy are also used. More and better treatments are being sought for this disease. The use of PARP inhibitors in the treatment of breast cancer has shown good results, so in this article we have done a review of the results of various studies on this topic. [1] In this review, the results of studies on the use of various PARP inhibitors in breast cancer of different hormonal status are presented. Purpose This article aims to give you an overview of the trials that have looked at the effects of different PARP inhibitors in the treatment of breast cancer. PARP inhibitors are a relatively new cancer therapy with good results, so it is important to pay attention. State of Knowledge In this article, I used the PubMed database and considered papers from the last 15 years, but most of the information in this review comes from papers published after 2020. I have also taken into account the recommendations of the FDA and the European Medicines Agency on the use of PARP inhibitors. Conclusions PARP inhibitors have shown significant effects on breast cancer outcomes. The differences in outcomes depending on the type of cancer, the PARP inhibitor used, and the previous therapies used in a given patient tell us how important it is to individualize therapy in oncology. The findings of the studies presented in this review also point to the need for further research that could focus on identifying patients who may best benefit from treatment with PARP inhibitors, as well as studying synergistic effects in combination with other forms of therapy, such as immunotherapy or chemotherapy. The changes in treatment outcomes that these drugs can bring underscore the importance of exploring new therapeutic strategies in oncology.